Dermatologic and otorhinolaryngologic manifestations in Leishmaniasis - Mota, Luiz Alberto Alves; Miranda, Roberta Ribeiro (Arquivos Internacionais de Otorrinolaringologia, 2011)
Introduction: Leishmaniasis is an extremely important parasitic disease as regards epidemiology, and, in such a disease, man is an occasional host to the Leishmania protozoon. Some of the major clinical, visceral and integumentary features are the mucocutaneous ways that can harm face and upper airways and even cause deforming lesions, leading to a functional impairment.Objective: Review the main dermatologic and otorhinolaryngologic manifestations in leishmaniasis.Methods: It was based on the Virtual Health Library (BVS), by entering the following keywords: Leishmaniasis, mucocutaneous leishmaniasis, nasal mucosa, and nose. References dated from 1999 to 2008 have been regarded.Final Comments: It is about a zoonosis, in which the human being is an occasional host attacked by Lutzomya or Phlebotomus insects that are, in turn, infected by the Leishmania parasite, and the early diagnosis of a leishmania-related lesion is essential, especially when a nasopharyngeal impairment is evident, with a view to preventing deformities or functional harms. The evaluation of cutaneous and/or mucosa lesions and the accurate definition of leishmaniasis diagnosis given by either dermatologists or otorhinolaryngologists enables the proper treatment to be implemented and the subsequent reduction in the disease dissemination.
Keywords: leishmaniasis; mucocutaneous leishmaniasis; nasal mucosa; nose